Analysis of Sustainability Report Compliance with GRI 303 and 304 at PT Aneka Tambang - Greta Calosa, Kristiana; Bayangkara, IBK (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to analyze the level of compliance of PT Aneka Tambang Tbk with sustainability reporting indicators based on the Global Reporting Initiative (GRI) 303 and GRI 304, which focus on water management and biodiversity, respectively. The method used is descriptive qualitative with a content analysis approach, which evaluates the extent to which the content of PT ANTAM’s 2023 Sustainability Report is in accordance with the indicators in the GRI Standards 2021. The results show that the company’s level of compliance with GRI 303 is 80%, while with GRI 304 is 100%. This finding indicates that the company is more consistent and comprehensive in reporting biodiversity aspects compared to water and effluent aspects. The implications of this study show the importance of transparency in sustainability reporting, especially in environmental aspects that have a direct impact on operational licenses and public legitimacy. The novelty of this study lies in the specific focus on two important aspects of environmental reporting and the application of qualitative analysis to recent reports from national mining companies. This research provides academic as well as practical contributions for companies in improving the quality and compliance of sustainability reporting.